2009
DOI: 10.1177/112067210901900513
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Visual Performance in 250 Eyes Implanted with the Tecnis ZM900 Multifocal IOL

Abstract: Purpose To evaluate visual performance in relation to time after implantation of the multifocal Tecnis intraocular lens (IOL) in patients with cataract. Methods This prospective case series involved 250 eyes of 137 patients with cataract aged 68.5±9.9 years. Monocular uncorrected and corrected near visual acuity (NVA and DCNVA) and distance visual acuity (UCVA and BCVA), occurrence of visual symptoms, and patient satisfaction were evaluated at 1–3 days, 30–90 days, and 150–210 days after surgery. Posterior c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 25 publications
(26 reference statements)
3
21
0
Order By: Relevance
“…The all optic zone diffractive rings of ZMB00 can induce more positive dysphotopsias than monofocal IOLs 22. In this study, the glare incidence rate was slightly higher in the multifocal group (14/25, 56.0%) than in the monofocal group (11/25, 44.0%), which fits in the previous study range 10 22 38 39. Our objective optical quality results suggested OSI in the monofocal group was significant better than in the multifocal group, and the results were consistent with the subjective results, which showed that moderate glare or halo was reported only in the multifocal group.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The all optic zone diffractive rings of ZMB00 can induce more positive dysphotopsias than monofocal IOLs 22. In this study, the glare incidence rate was slightly higher in the multifocal group (14/25, 56.0%) than in the monofocal group (11/25, 44.0%), which fits in the previous study range 10 22 38 39. Our objective optical quality results suggested OSI in the monofocal group was significant better than in the multifocal group, and the results were consistent with the subjective results, which showed that moderate glare or halo was reported only in the multifocal group.…”
Section: Discussionsupporting
confidence: 91%
“…Dysphotopsias can be caused by either multifocal or monofocal IOLs, and it includes both positive and negative dysphotopsias 10 22 38 39. The all optic zone diffractive rings of ZMB00 can induce more positive dysphotopsias than monofocal IOLs 22.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current series, a low level of halo perception was reported in 60% of patients at 6 months postoperatively, with no severe complaints of halos. Future studies should confirm if this subjective symptomatology disappears with time, as suggested by many authors based on the short- and medium-term outcomes [15] and according to the significant reduction of the intensity of photic phenomena with time observed in the current series.…”
Section: Discussionsupporting
confidence: 70%
“…Several factors may have contributed to this finding, but patient neuroadaptation to the multifocality induced by the IOL optics seems to have played a major role. Indeed, a similar finding has been reported with other diffractive multifocal IOLs [14,15] and it has even been demonstrated that visual performance after multifocal IOL implantation can be significantly accelerated by training programs [16]. Via the neuroadaptation process (synaptogenesis, neurogenesis) [17], the brain has the ability to select an image related to the object that is being looked at, suppressing other images.…”
Section: Discussionsupporting
confidence: 62%